Sustainable Development in Africa: Fostering Sustainability in One of the Worlds Most Promising Continents - Filho, Walter Leal; Rudi Pretorius; Luiza Olim de Sousa (South Africa Springer, 2021)
This book serves the purpose of documenting and promoting African experiences on sustainable development, which encompasses both, formal and non-formal education. Sustainable development is very important to Africa, but there is a paucity of publication which documents and promotes experiences from African countries. Due to their complexity, the interrelations between social, economic and political factors related to sustainable development, especially at universities, need to be better understood. There is also a real need to showcase successful examples of how African institutions are handling their sustainability challenges.
Bibliography 739p-741p
Keywords: Sustainable Development